Beyond words: an investigation of fine motor skills and the verbal communication spectrum in autism - Simarro Gonzalez, Marian; Ni, Gessica; Lam, Valerie; Demopoulos, Carly (Frontiers in Psychiatry, 2024)
This study investigated the associations between fine motor skills and expressive verbal abilities in a group of autistic participants aged 8 to 17 years. Based on prior research, we hypothesized that individuals on the autism spectrum would exhibit deficits in fine motor speed, dexterity, pencil motor control, but not manual motor strength. Additionally, we expected that impaired fine motor skills would be linked to poorer performance on standardized measures of verbal abilities. The results indicated that 80% of autistic participants demonstrated an impairment on at least one measure of motor skills, and as a group, they exhibited significantly poorer fine motor performance compared to the non-ASD group in dominant hand finger tapping speed, bilateral fine motor dexterity measured via the grooved pegboard task, and pencil motor coordination and visual-motor integration measured on the Beery-Buktenica Developmental Test of Visual-Motor Integration-Sixth EditionBeery VMI. Moreover, impaired fine motor skills were associated with poorer performance on standardized clinical measures of verbal abilities, including articulation errors, receptive and expressive language and vocabulary, rapid naming, oromotor sequencing, and parent reported functional communication skills and social communication symptoms. Overall, our findings suggest there is a high prevalence of fine motor impairments in ASD, and these impairments were associated with a range of verbal abilities. Further research is warranted to better understand the underlying mechanisms of these associations and develop targeted interventions to address both fine motor and verbal impairments in ASD.